'A Local Habitation and a Name' On the Images of John's Apocalypse - Guffey, Andrew R. (2018)
The images of the book of Revelation have always presented interpreters with challenges. How are we to understand these images? What models or comparand a might produce valuable insights into their use? What is accomplished by such strange language? This paper argues that a central aspect of the images has been frequently overlooked in interpretations of the book of Revelation: their visuality. While visual realia and ancient rhetoric have been employed in the service of interpreting Revelation, they have not frequently been used specifically to unravel the riddle of the imagistic language of the book. By interrogating visual comparanda and drawing on ancient discourse on ekphrasis (vivid description), we can begin to grasp the power of John’s images, which was to “present” his audience(s) with a virtual visual reality that subtly countered the imagination of the divine inscribed in the visual culture of the cities of Asia Minor.
Keywords: Apocalypse in literature; Bible. Revelation; Criticism, Literary; Ekphrasis; Revelation; Biblical teaching; Symbolism; Visualization